Morphological changes of the hepatobiliary system and salivary glands under the influence of stress - Denefil, Olha; Chorniy, Sofiia; Romanovych, Viktoriia; Levkiv, Mariana; Chornij, Natalia; Tverdokhlib, Natalia; Gryniuka, Iurii (Journal of Education, Health and Sport, 2023)
Stress can impact our bodies at the cellular level, causing changes to various organs and systems. Chronic stress can indirectly affect the hepatobiliary tract. Salivary gland dysfunction can be a manifestation of a large variety of systemic diseases or the consequence of local structural or functional pathologies. Stress can influence the oral microbiome, leading to changes in microbial diversity. Scientists study stress reactions, new resistance methods, and modern approaches to prevent and treat stress. The aim is to examine the morphological aspects and changes of the blood vessels in the liver and salivary glands of white rats in experiment using acute immobilization stress. Materials and methods. In total 22 white male rats were studied, divided into two groups. The first was kept as a control, the second was subjected to acute immobilization stress. The rats were immobilized by hanging them by the neck with a clamp for 6 hours. Animals were euthanized with a sodium thiopental solution. Samples of the liver and parotid gland were examined histologically using hematoxylin and eosin stain. Results. The livers of rats were studied after acute immobilization stress. Significant changes were observed in the liver blood vessels, including thrombosis and expansion of perisinusoidal spaces. Liver cells also showed changes such as karyopyknosis, colliquation necrosis, and hydropic dystrophy. The parotid salivary gland histologic examination showed swelling in the connective tissue, periductal regions, and perivascular spaces. In the acinar section, basophilia and swelling of serocytes were observed, along with dystrophic processes leading to remodeling of the acini and ducts. The narrowing of arterioles was observed, reflecting tension in the arterial system. Conclusions. Exposure to acute stress can cause changes in the liver and biliary tract, increasing the risk of various diseases, including those that affect the oral cavity.